Estimating hurricane evacuation destination and accommodation type selection with perceived certainty variables. (April 2022) - Adjei, Emmanuel; Murray-Tuite, Pamela; Ge, Yue; Ukkusuri, Satish; Lee, Seungyoon
Highlights: Data come from a survey of residents of Jacksonville, FL after Hurricane Matthew. MNL models identify factors associated with accommodations and destinations. Greater hurricane graphics understanding decreased the probability of staying in the area. Greater certainty of hurricane impact location decreased the probability of going southeast. Greater certainty of hurricane impact time increased the probability of staying in a home. Abstract: This paper investigates how perceived certainty factors influenced households' selection of destination and accommodation type during evacuation. Using survey responses from Jacksonville, FL, multinomial logit models were developed for both choices. For the first, greater understanding of hurricane-related graphics decreased households' probability of staying within their community. Households with a member who has special medical needs and those evacuating with a greater number of vehicles were more likely to stay in the eastern portion of their county. Greater perceived certainty about the hurricane impact location decreased households' probability of evacuating to the south. For the accommodation model, married evacuees and those who received official evacuation notices had increased likelihood of staying in hotels/motels, while those who evacuated a day before landfall were less likely to do so. Greater perceived certainty about hurricane impact time and frequency of communication with social network members increased the probability of staying in a peer's home.